2018
DOI: 10.1093/jac/dky261
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to R-pyocins of Pseudomonas aeruginosa clinical isolates from cystic fibrosis patients

Abstract: Our results highlight the possibility of using R-pyocins as therapeutic agents, alone or as adjuvants, against P. aeruginosa in cystic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…While we expect that some strains may in fact produce R-pyocins but were unable to be typed due to sequencing or contig errors, it is possible that many of these strains may not possess R-pyocins at all. Another group evaluating R-pyocin susceptibility among 34 CF isolates found that 23 (68%) of their isolates did not produce R-pyocins or could not be typed (69). This suggests that CF isolates of P. aeruginosa may lose the ability to produce R-pyocins later in chronic infection, but more work is necessary to confirm this phenotype and explore the potential fitness advantages of this evolutionary trajectory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While we expect that some strains may in fact produce R-pyocins but were unable to be typed due to sequencing or contig errors, it is possible that many of these strains may not possess R-pyocins at all. Another group evaluating R-pyocin susceptibility among 34 CF isolates found that 23 (68%) of their isolates did not produce R-pyocins or could not be typed (69). This suggests that CF isolates of P. aeruginosa may lose the ability to produce R-pyocins later in chronic infection, but more work is necessary to confirm this phenotype and explore the potential fitness advantages of this evolutionary trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have R-pyocin typed single isolates of P. aeruginosa from CF patients and compared R-types from longitudinal collections of single isolates (58,69). The typing of single isolates does not consider the genotypic and phenotypic diversity of P. aeruginosa which evolves over the course of chronic infection (2-4, 10-12, 14-16).…”
Section: Discussionmentioning
confidence: 99%
“…These bacteriocins often possess a narrow spectrum of antimicrobial activity against closely related strains and so are likely to be involved in interstrain competition. Recently it has been shown that strains of P. aeruginosa isolated from CF lungs are particularly susceptible to R-pyocins, mainly due to their LPS architecture with nontypeable or non-accessible O-serotypes (22).…”
Section: Discussionmentioning
confidence: 99%
“…O antigen likely also protects P. aeruginosa from the killing effects of S pyocins since studies in enterics have shown that the O antigen chain length and density are important factors in protecting them against colicins [160][161][162]. Interestingly, since a high proportion of CF isolates are susceptible to at least one subtype of R pyocin, the use of pyocin cocktails could potentially be viewed as highly targeted therapeutics to treat chronic infections in CF patients [163]. Indeed, the efficacy of a number of pyocins has been demonstrated in in vivo animal models [164][165][166][167].…”
Section: Phages and Pyocinsmentioning
confidence: 99%